A retrospective study of implants placed following 1‐stage or 2‐stage maxillary sinus floor augmentation by the lateral window technique performed on residual bone of <4 mm: Results up to 10 years of follow‐up. Issue 2 (2nd August 2019) - Kim, Hyun Ju; Yea, Sanghyun; Kim, Kyoung‐Hwa; Lee, Yong‐Moo; Ku, Young; Rhyu, In‐Chul; Seol, Yang‐Jo
Abstract: Background: The purpose of this study was to compare the survival rates of implants placed following 1‐stage or 2‐stage maxillary sinus floor augmentation by the lateral window technique (SFALW) performed on residual bone of <4 mm. Methods: This study was conducted based on dental records and radiographs obtained from patients who received SFALW from March 2006 to June 2014, being followed up between March 2006 and December 2017. They were divided into 1‐stage and 2‐stage groups according to the SFALW performed. Statistical analysis was performed to evaluate whether a significant difference existed between 1‐stage and 2‐stage SFALW in terms of survival rates. Multivariable logistic regression analysis was used to examine the influence of multiple variables on implant failure. Results: A total of 395 implants (156 implants in the 1‐stage group, 239 implants in the 2‐stage group) in 167 patients fulfilled the inclusion criteria. Among them, 13 implants (five implants in the 1‐stage group, eight implants in the 2‐stage group) failed. No significant difference was found in the 10‐year cumulative survival rate of implants between the 1‐stage group and the 2‐stage group (96.8% and 92.5%, respectively, P = 0.656). Multivariable logistic regression analysis demonstrated that implant failure was significantly influenced by implant length and functional time following prosthetic loading. Conclusions: The 10‐year cumulative survival rates showed no statistically significant difference between implants following 1‐stage and 2‐stage maxillary SFALW performed on residual bone height of <4 mm.